Economic activity and congenital anomalies: An ecologic study in Argentina - Castilla, Eduardo Enrique (2000)
In this study, we analyze the association between industrial activity and the occurrence of 34 congenital anomalies. We selected 21 counties in Argentina during 1982-1994 and examined a total of 614,796 births in these counties in consecutive series. We used the International Standard Industrial Classification of All Economic Activities as an indicator of exposure to 80 specific industrial activities. Incidence rate ratios for each congenital anomaly were adjusted by the socioeconomic level of the county according to a census index of social deprivation. For a given exposure/anomaly association to be considered as significant and relevant, the exposure had to be a statistically significant risk for the occurrence of the anomaly and an increase in the birth prevalence rate of the congenital anomaly type involved had to be observed in those counties where the putative causal activity was being performed. Significant associations (p < 0.01) were identified between textile industry and anencephaly, and between the manufacture of engines and turbines and microcephaly. These observations are consistent with previous reports on occupational exposure, and their further investigation by means of case-control studies is recommended.